Clutter model in modeling growth and yield of eucalyptus in crop‑livestock‑forest integration systems - Salles, Thiago Taglialegna; Leite, Helio Garcia; de Oliveira Neto, Sílvio Nolasco; Soares, Carlos Pedro Boechat; de Paiva, Haroldo Nogueira; dos Santos, Fabiano Lourenço (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to define the best form of use of the Clutter model, in order to estimate growth and yield of eucalyptus clones in crop‑livestock‑forest integration systems. Data were collected from integration systems located in the northwest region of the state of Minas Gerais, Brazil. The data were originated from 180 continuous inventory permanent plots of 30x40 m, with three ten‑plant rows and stratified random sampling of one plot per 10 ha. The average number of trees per hectare was 242. Plants with ages from 20 to 95 months were evaluated. The best functional relationships were obtained using the original Clutter model, based on the significance and on the expected signs of its estimated parameters. The Clutter model should be adjusted on its unreduced form.